Germline BRCA1 and BRCA2 mutations and the risk of bladder or kidney cancer in Poland - Elżbieta Złowocka-Perłowska; Aleksandra Tołoczko-Grabarek; Steven A. Narod; Jan Lubiński (Hereditary Cancer in Clinical Practice, 2022)
Abstract Introduction The role of the BRCA1 and BRCA2 genes in bladder and renal tumorigenesis is unclear. Our goal was to determine the prevalence of specific founder mutations genes BRCA1 (5328 insC, C61G and 4153 delA) and BRCA2 (C5972T) mutations in bladder and kidney cancer patients from Poland. Materials and methods We genotyped 1028 patients with bladder cancer and 688 cases with kidney cancer and two control groups. Results A BRCA1 mutation (all variants combined) was detected in peripheral blood leukocytes in 5 out of 1028 (0.5%) bladder cases and in 17 of 4000 controls (0.4%) (odds ratio [OR], (OR = 1.1; 95% CI 0.42–3.11; p = 1.0). Among 688 unselected kidney cancer cases a BRCA1 mutations was reported in three patients (0.4%) (OR = 1.0; 95% CI 0.29–3.51; p = 1.0). The mutation C5972T in BRCA2 was observed in 54 bladder cancer patients (5.2%) and in 159 of 2791 healthy controls (5.7%) (OR = 0.9; 95% CI 0.66–1.26; p = 0.6). Fifty kidney cancer cases carried a BRCA2 mutation (7.3%) (OR = 1.3; 95% CI 0.93–1.80; p = 0.1). Conclusion In conclusion, we found no difference in the prevalence of BRCA1 and BRCA2 founder mutations between cases and healthy controls. The mutations BRCA1 and BRCA2 seem not to play a role in bladder and kidney cancer development in Polish patients.